TAFSIR AL-MAIDAH 51 PERSPEKTIF HERMENEUTIKA PEMBEBASAN: TELAAH DAN IMPLEMENTASI PEMIKIRAN FARID ESACK - Sidiq Permana, Fadhila (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
The discussion about al-Maidah 51 was widely discussed, especially when a non-Muslim governor candidate emerged a few years ago. In al-Maidah 51 there is a text that prohibits making Jews and Christians helpers. That is what is then understood by some circles as a prohibition on appointing non-Muslim leaders. Farid Esack has the idea of liberation hermeneutics in understanding the Qur'an. The hermeneutics of liberation aims to fight all forms of oppression, including oppression in the form of identity politics. Esack said that an interpreter should understand God's ideas in the Qur'anic text, understand the keys of teachings such as justice, piety, monotheism, understanding of al-mustadh'afun (the weak and oppressed). Esack also explained that the Qur'an is inseparable from the historical context that is the background, even though the Qur'an descended in the context of Makkah and Medina at that time, the Qur'an still has significance with other new contexts. So when one wants to understand al-Maidah 51 in the Indonesian context, one must first understand what is the reason why God forbade Jews and Christians to be helpers at that time. In the book of tafsir, it is explained that the reason for the prohibition is the existence of a negative character that perches in a person and a liver disease in the form of hypocrisy. It is this negative character that causes humans not to be used as helpers. So when al-Maidah 51 is understood in the Indonesian context, it will certainly give birth to different interpretation products. Because negative character and heart disease in the form of hypocrisy can affect people of any religion, including from Islam itself which is the majority group in Indonesia.